Mass transfer characteristics of ferrofluids flowing through a microchannel under AC magnetic field. (December 2022) - Akbari, Pariya; Haghshenasfard, Masoud; Esfahany, Mohsen Nasr; Ehsani, Mohammadreza
Abstract: The gas absorption process in a Y-shaped microchannel utilizing magnetic nanofluids stimulated within an alternating current magnetic field (AC mf) was studied. Absorption of CO2 under different operation conditions, ferrofluid concentration, and magnetic field strengths were investigated to analyze the liquid-side overall mass transfer coefficient (KL a), CO2 absorption efficiency (E), nanoparticle enhancement factor (α), magnetic field enhancement factor (γ), and pressure drop (Δp). The magnetic field strengths were 7, 12.6, and 21 mT accompanied by various ferrofluid concentrations within 0.001–0.004 ( v /v). The ferrofluids were water-based colloids of Fe3 O4 magnetic nanoparticles. The gas-liquid flow patterns were Taylor flow regime in all experiments. Furthermore, the position of the microchannel in the magnetic field was studied as an effective factor in CO2 absorption enhancement. The position in which the microchannel was held on the top inside the magnetic field reflected more gas absorption compared to the other positions. While exerting magnetic field strength of 21 mT, a maximum enhancement of 72.2% was observed for KL a compared to the case in which the magnetic field was absent. Highlights: A magnetic field is an effective parameter on CO2 absorption rate and pressure drop. Mass transfer coefficient in nanofluid is higher in comparison with pure water. The use of a magnetic field increases the mass transfer rate. The pressure drop increases by increasing the nanofluid concentration.